Crystal structure of pentakis(ethylenediamine-κ(2) N,N′)lanthanum(III) trichloride–ethylenediamine–dichloromethane (1/1/1) - Sartain, Hope T. (Acta Crystallogr Sect E Struct Rep Online, 2014)
We report here the crystal structure of a ten-coordinate lanthanum(III) metal coordinated by five bidentate ethylenediamine ligands, [La(C(2)H(8)N(2))(5)]Cl(3)·C(2)H(8)N(2)·CH(2)Cl(2). One free ethylenediamine molecule and three Cl(−) anions are also located in the asymmetric unit. The overall structure is held together by an extensive hydrogen-bonding network between the Cl(−) anions and the NH groups on the metal-bound ethylenediamine ligands. The free ethylenediamine molecule is held in an ordered position by additional hydrogen bonds involving both the chlorides and –NH groups on the metal-bound ligands. One highly disordered molecule of dichloromethane is located on an inversion center; however, all attempts to model this disorder were unsuccessful. The electron density in this space was removed using the BYPASS procedure [van der Sluis & Spek (1990 ▶). Acta Cryst. A46, 194–201].